2021
DOI: 10.1021/acs.jpclett.1c02472
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite Quantum Dots with Ultrahigh Solid-State Photoluminescence Quantum Efficiency, Superior Stability, and Uncompromised Electrical Conductivity

Abstract: All-inorganic perovskite quantum dots (PQDs), potentially applicable to high-performance display technologies, are facing challenges when the superior luminescence properties with high stability and uncompromised electrical conductivity are combined. Here, by introducing hexylamine sulfate and reducing the reaction rate, we managed to optimize the surface sacrificial coating of CsPbBr3 QDs. As a result, the colloidal PQDs show a photoluminescence quantum efficiency (PLQE) of 95.8% in solution, and an internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…[110,113] However, traps in PSNCs are related to the surface of the nanostructures and their passivation can eliminate undesirable energy states. [103,104,110,114] Further, several reports have indicated the strong effect of capping agents such as trimethylaluminum, di-dodecyl dimethyl ammonium bromide, hexylamine sulfate, or NH 4 SCN on the emission efficiency of PSNCs. [110,115,116] The most impressive emission efficiency (PL quantum yield (PLQY) close to unity) was achieved by capping CsPbBr 3 NCs with NH 4 SCN and hexylamine sulfate, which effectively removed the excess lead from the surface.…”
Section: Perovskite Nano Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…[110,113] However, traps in PSNCs are related to the surface of the nanostructures and their passivation can eliminate undesirable energy states. [103,104,110,114] Further, several reports have indicated the strong effect of capping agents such as trimethylaluminum, di-dodecyl dimethyl ammonium bromide, hexylamine sulfate, or NH 4 SCN on the emission efficiency of PSNCs. [110,115,116] The most impressive emission efficiency (PL quantum yield (PLQY) close to unity) was achieved by capping CsPbBr 3 NCs with NH 4 SCN and hexylamine sulfate, which effectively removed the excess lead from the surface.…”
Section: Perovskite Nano Crystalsmentioning
confidence: 99%
“…[110,115,116] The most impressive emission efficiency (PL quantum yield (PLQY) close to unity) was achieved by capping CsPbBr 3 NCs with NH 4 SCN and hexylamine sulfate, which effectively removed the excess lead from the surface. [110,114] In addition, timeresolved TA and PL measurements revealed that the passivation of MAPbBr 3 QDs by n-octylamine resulted in the elimination of trap-assisted recombination. [103] The passivation of the QD surface caused the faster decay component to disappear, and both TA and PL decays were composed of one component because of the bimolecular recombination.…”
Section: Perovskite Nano Crystalsmentioning
confidence: 99%
“…A higher quantum yield with narrow FWHM (full width of half maximum) allows an intense fluorescence emission and the confined size range in these perovskite quantum dots results in stronger quantum confinement leading to narrow emission bands. 1 These factors and the faster photoluminescence (PL) decay of CQDs that occurs at higher emission energies, all together make PQDs attractive over CQDs. The highly volatile nature of organic (A) cations in these PQDs of the ABX 3 structure is known to result in faster degradation than that of the all-inorganic PQDs.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Perovskite quantum dots have the advantages of high PLQY, low cost and solution processing, which are suitable for inkjet printing. 3,4 The efficiency of spin-coated perovskite light-emitting diodes has developed rapidly. In just a few years, the efficiency of red and green perovskite LEDs has exceeded 20%, and the blue perovskite LED has reached 12%.…”
Section: Introductionmentioning
confidence: 99%